Schools of democracy: how trade union membership impacts political participation in Africa's emerging democracies. Issue 1 (2nd January 2018) - Karreth, Ann K.
ABSTRACT: Trade unions in Africa have become increasingly vocal in calling attention to the widening socio-economic inequalities that have accompanied global market integration across the continent. This article argues that, in their quest to challenge neoliberal policies, labour movements have contributed to processes of democratization in Africa by acting as instruments of political socialization for their members. Using survey data from respondents in 18 African countries, this article demonstrates an empirical relationship between trade union membership and political participation. The article finds that membership in a labour organization increases one's propensity to participate in a range of political activities. Specifically, labour movements encourage participation by forging "participatory spillover effects", which mobilize unionists across different arenas of the political landscape. Finally, the article finds that the effect of union membership on political participation is stronger in countries where unions maintain independence from ruling parties. This research contributes to literature on political participation across Africa and furthers our understanding of the role of labour movements in bottom-up processes of democratization on the continent.